2002
DOI: 10.1021/jf020513k
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Spectroscopic Study of β-Lactoglobulin Interactions with Two Flavor Compounds, γ-Decalactone and β-Ionone

Abstract: Interactions between a well-characterized protein, beta-lactoglobulin, and two flavor compounds, beta-ionone and gamma-decalactone, were studied by 2D NMR spectroscopy. NMR spectra were recorded in aqueous solution (pH 2.0, 12 mM NaCl, 10% D(2)O) under conditions such that beta-lactoglobulin is present in a monomeric state. TOCSY and NOESY spectra were recorded on the protein and the complexes between protein and ligands. The spectra of the NH-CH(alpha) region showed the cross-signals due to the coupling betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 40 publications
1
32
0
Order By: Relevance
“…Based on the literature results stating that fatty acids bind in the central hydrophobic pocket of BLG [18], it was concluded that the above-mentioned substances have the same binding position. Different behavior was found for the binding of b-ionone to BLG and this was confirmed by the 2D-NMR study of Lübke et al [19]. The 2D-NMR results suggested binding of g-decalactone (pH 2.0) in the central hydrophobic pocket of BLG and, for b-ionone, an external binding site in a groove on the outer surface of BLG that is built up by the helix and the external part of the b-barrel.…”
Section: à7mentioning
confidence: 57%
See 1 more Smart Citation
“…Based on the literature results stating that fatty acids bind in the central hydrophobic pocket of BLG [18], it was concluded that the above-mentioned substances have the same binding position. Different behavior was found for the binding of b-ionone to BLG and this was confirmed by the 2D-NMR study of Lübke et al [19]. The 2D-NMR results suggested binding of g-decalactone (pH 2.0) in the central hydrophobic pocket of BLG and, for b-ionone, an external binding site in a groove on the outer surface of BLG that is built up by the helix and the external part of the b-barrel.…”
Section: à7mentioning
confidence: 57%
“…From these results, one can expect a binding position of g-decalactone to BLG, which is different from that of the central hydrophobic pocket. In contrast, 2D-NMR studies at pH 2.0 [19] and molecular-modelling investigations [13] suggested binding of g-decalactone in the central hydrophobic pocket of BLG.…”
mentioning
confidence: 91%
“…Based on estimated affinity values, the semi-empirical classifying procedure led to obtaining three subsets: Mapping of compounds from group S21 on the best significant hypothesis of group S21 surprisingly showed that β-ionone 27 and γ -decalactone 33 were in good alignment, even when NMR observation pointed out two different binding regions on the BLG. 10 We noted an underestimation of S21 compounds by the best significant hypothesis generated by group P24 and an overestimation of P24 compounds by the best significant hypothesis generated by group S21. There is an assumption that this ensemble of compounds is related to the same binding site, which is able to undergo conformational changes according to experimental conditions.…”
Section: Catalyst 3d-qsar Studymentioning
confidence: 59%
“…[4][5][6][7][8]10 Thus, Catalyst confirms the existence of at least two binding sites on the BLG. It strongly suggests that some ligands recognize specifically the same binding site.…”
Section: Catalyst 3d-qsar Studymentioning
confidence: 59%
See 1 more Smart Citation